Analysis of Financial Performance and Its Impact on the Growth of MSMEs in the Manufacturing Sector in Yogyakarta - Ivandi Maulana Laba; Rinaldi Rinaldi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of financial performance on the growth of Micro, Small, and Medium Enterprises (MSMEs) in the manufacturing sector in Yogyakarta. Financial performance in this study was measured using Liquidity Ratio (Current Ratio), Solvency (Debt to Equity Ratio), Activity (Total Asset Turnover), and Profitability (Return on Assets). This study uses a quantitative approach with multiple linear regression analysis methods. The research sample consists of 50 active manufacturing MSMEs selected purposively during the period 2022 to 2024. Data is collected through questionnaires and financial statement documentation. The results of the study show that the ratio of activity and profitability has a significant effect on business growth, while the ratio of liquidity and solvency has no significant effect. These findings show that operational efficiency and profit-generating ability are key factors in driving MSME growth. This research contributes to MSME actors in improving financial management, as well as being the basis for local governments in designing sustainable financial training programs.